2017
DOI: 10.1002/ajoc.201700248
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Curtius Rearrangement Approach for the Synthesis of Unsymmetrical Sulfonimidoyl Ureas

Abstract: Ah ighly efficient synthesis of unsymmetrical sulfoximineu reas is developed. Ther eactionu nites simple NH-sulfoximines and acyl azides by af ormal Curtius rearrangementa st he key step. This reaction could be easily scaled up to gram scale and omits the generation of hazardous byproducts, thusa llowing ap ractical and environmentally benignp ath for the synthesis of medicinally important sulfonimidoyl unsymmetrical ureas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…These reactions each combined a simple NH‐sulfoximine and an acyl azide through a formal Curtius rearrangement, which was the key step (Scheme 24). [53] This class of reactions complements those of previous reports using isocyanates and carbamoyl chlorides.…”
Section: Transformations Of Sulfoximinessupporting
confidence: 81%
“…These reactions each combined a simple NH‐sulfoximine and an acyl azide through a formal Curtius rearrangement, which was the key step (Scheme 24). [53] This class of reactions complements those of previous reports using isocyanates and carbamoyl chlorides.…”
Section: Transformations Of Sulfoximinessupporting
confidence: 81%
“…As it turned out, the sulfides derived from aldehydes 7-9 and 11 failed to undergo a rearrangement ( [13][14][15][16][17][18]. This sulfur atom phosphorus-to-carbon migration in phosphine sulfides has previously been mentioned only once in the literature [59].…”
Section: Methodsmentioning
confidence: 93%
“…Among all organic reactions, rearrangements are an exciting class of transformations where unusual or even unexpected products can be obtained. Many rearrangements are of practical use in synthetic organic chemistry, including Beckmann [1][2][3][4], Claisen [5][6][7][8], pinacol [9][10][11][12], Wagner-Meerwein [13][14][15][16], Curtius [17][18][19][20], Hofmann [21][22][23][24], Overmann [25][26][27][28] rearrangements, and many others. In organophosphorus chemistry, rearrangements are less developed transformations, however, some examples can be found in the literature (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…A different approach for the N‐functionalization of NH‐sulfoximines, was developed by Chen and coworkers. [113] The authors reported a Curtius rearrangement‐based approach for the synthesis of sulfonimidoyl ureas 41 under metal‐free conditions (Scheme 42 , a). The reaction enabled a straightforward preparation of sulfonimidoyl ureas by mixing NH‐sulfoximines 3 and acyl azides in acetonitrile at 80 °C.…”
Section: Recent Developments In the Functionalization Of Nh‐sulfoximinesmentioning
confidence: 99%